General fabrication of RuM (M = Ni and Co) nanoclusters for boosting hydrogen evolution reaction electrocatalysis. Issue 30 (22nd July 2021) - Yuan, Mengyu; Wang, Cheng; Wang, Yong; Wang, Yuan; Wang, Xiaomei; Du, Yukou
Abstract : RuM (M = Ni and Co) nanoclusters supported by carbon fiber cloths are prepared as an efficient electrocatalyst for the HER. Abstract : Rational design and fabrication of highly active electrocatalysts toward the hydrogen evolution reaction (HER) are of paramount significance in industrial hydrogen production via water electrolysis. Herein, by taking advantage of the high surface-to-volume ratio, maximized atom-utilization efficiency, and quantum size effect, we have successfully fabricated an innovative class of Ru-based alloy nanoclusters. Impressively, carbon fiber cloth (CFC) supported RuNi nanoclusters could exhibit outstanding electrocatalytic performance toward the HER, in which the optimal composition RuNi/CFC could achieve a current density of 10 mA cm −2 with an overpotential of merely 43.0 mV in 1 M KOH electrolyte, as well as a low Tafel slope of 30.4 mF dec −1 . In addition to the high HER activity in alkaline media, such Ru-based alloy nanoclusters are also demonstrated to be highly active and stable in acidic solution. Mechanistic studies reveal that the alloying effect facilitates water dissociation and optimizes hydrogen adsorption and desorption, thereby contributing to the outstanding HER performance. This work paves a new way for the rational fabrication of advanced electrocatalysts for boosting the HER.